INSTITUTIONS OF HIGHER EDUCATION PEDAGOGICAL JUSTIFICATION OF INCREASING THE EFFICIENCY OF PHYSICAL EDUCATION LESSONS - Mukhammadiev Kamil Burkhanovich (Scholars Digest Publishing, 2023)
This article discusses the features of the organization and conduct of physical education and sports in the field with such indicators as physical training of students in technical universities, passing test standards in the process of physical education, anthropometric indicators, heart rate. The relevance of the topic, goals and objectives are based on a scientific point of view and skillfully moving forward.
Keywords: physical culture and sport, body, exercise, healthy lifestyle, skills, physical culture, development, popularization, speed, agility, flexibility, endurance, strength, physical training